Electrical, thermal behaviors and synthesis of intramolecular cobalt phthalocyanine with single-chain polymer structure - Biryan, Fatih; Tuncer, Hulya; Demirelli, Kadir (Springer, 2020)
Firstly, poly[4-(4-vinylbenzyl)oxy)phthalonitrile]-co-styrene, [poly(VBOP-co-St], which is used as a linear copolymer precursor containing phthalonitrile pendant group was prepared from copolymerization of VBOP and St by atom transfer radical polymerization method at 110 degrees C. Then, complex synthesis of cobalt phthalocyanine in the single-chain polymer (SCP-CoPc complex) via the intramolecular macrocyclization reaction of cobalt and phthalonitrile group in poly(VBOP-co-St) was carried out at 150 degrees C in the presence of excess cyclohexanol. Both linear copolymer precursor and formation of cobalt phthalocyanine within a single-chain polymer were confirmed by FT-IR, H-1-NMR, C-13-NMR and UV/Vis spectroscopy techniques. Particularly, the formation of SCP-CoPc complex was characterized by almost disappearance of -C equivalent to N band at 2230 cm(-1) of the FT-IR and appearance of Q band around 672 nm and the B band in the near UV region at 350 nm of UV/Vis spectroscopy. The pure poly(VBOP-co-St), SCP-CoPc complex and the residue SCP-CoPc complex heated to 500 degrees C were characterized by SEM images, and the element analyses were estimated from X-ray energy dispersive spectroscopy (X-ray EDS). The EDS elemental analysis results of the residual of SCP-CoPc complex degraded to 500 degrees C showed that CoO [cobalt(II)oxide] compound occurred. The thermal properties of poly(VBOP-co-St) and SCP-CoPc complex were investigated through thermogravimetric analysis and differential scanning calorimeter. The conducting nanographene-based SCP-CoPc composites were prepared. DC and AC electrical conductivity and dielectric properties were investigated. The ac dielectric measurements of poly(VBOP-co-St), SCP-CoPc complex and composites were investigated at room temperature between 100 and 20 kHz depending on the alternating current conductivities. Also, the activation energy profile of SCP-CoPc/4% (by wt) nanographene composite was revealed by measuring the DC conductivity of individual composite material.
Keywords: Phthalocyanine; Nanographene; Electrical measurements; Thermal behavior; Synthesis